A 1-year trial of repeated high-dose intravenous iron isomaltoside 1000 to maintain stable hemoglobin levels in inflammatory bowel disease. (October 2015) - Reinisch, Walter; Altorjay, Istvan; Zsigmond, Ferenc; Primas, Christian; Vogelsang, Harald; Novacek, Gottfried; Reinisch, Sieglinde; Thomsen, Lars L.
Abstract Objective. Iron isomaltoside 1000 (Monofer®) is a high-dose intravenous (IV) iron, which in a recent 8 weeks trial in inflammatory bowel disease (IBD) subjects with iron deficiency anemia (IDA) demonstrated good tolerability and efficacy. The present trial is an extension to this trial, which evaluates the need for additional high IV iron doses to maintain a stable hemoglobin (Hb) ≥12.0 g/dl. Material and methods. This was a prospective, open-label, 12 months trial of European IBD subjects willing to participate after completing the lead-in trial. Subjects were allowed re-dosing with 500–2000 mg single doses of iron isomaltoside 1000 infused over ∼15 min at 3 months intervals depending on a predefined algorithm. Outcome measures included Hb, safety parameters and need for additional iron dosing. Results. A total of 39 subjects were enrolled of which 34 subjects required re-dosing with a median cumulative 1-year dose of 1.8 g (mean cumulative dose 2.2 g). The mean (SD) Hb was 12.3 (1.5) g/dl at baseline, 12.8 (1.6) g/dl at 3 months, 12.8 (1.6) g/dl at 6 months, 12.9 (1.4) g/dl at 9 months and 12.9 (1.6) g/dl at 12 months. Seventy-four percent of subjects who had an Hb ≥12.0 g/dl at baseline were able to maintain Hb ≥12.0 g/dl till the end of the trial at 12 months. Nonserious probably related hypersensitivity reactions without significant hypotension were reported at the beginning of the infusion in two subjects, who recovered without sequelae. Conclusion. Repeated treatment of iron deficiency with iron isomaltoside 1000 could avoid episodes of IDA without major safety issues.